2015
DOI: 10.1039/c5ta05769h
|View full text |Cite
|
Sign up to set email alerts
|

O3-type layered transition metal oxide Na(NiCoFeTi)1/4O2 as a high rate and long cycle life cathode material for sodium ion batteries

Abstract: High rate capability and long cycle life are challenging goals for the development of room temperature sodium-ion batteries. Here we report a new single phase quaternary O3-type layer-structured transition metal oxide Na(NiCoFeTi)1/4O2 synthesized by a simple solid-state reaction as a new cathode material for sodium-ion batteries. It can deliver a reversible capacity of 90.6 mAh g -1 at a rate as high as 20C. At 5C, 75.0% of the initial specific capacity can be maintained after 400 cycles with a capacity-decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 23 publications
6
56
0
Order By: Relevance
“…The electrochemical Na-ion intercalation behavior of layered transition-metal oxides was examined by Delmas and co-workers in the early 1980s. The significant role of the inactive Ti ions in promoting the battery performance of layered sodium-containing electrodes is also found in other reports [39][40][41][42] and has been reviewed in a previous paper. However, these authors have identified many structural properties of layered and trigonal-prismatic interstitial sites, respectively.…”
Section: Layered Transition-metal Oxidessupporting
confidence: 63%
“…The electrochemical Na-ion intercalation behavior of layered transition-metal oxides was examined by Delmas and co-workers in the early 1980s. The significant role of the inactive Ti ions in promoting the battery performance of layered sodium-containing electrodes is also found in other reports [39][40][41][42] and has been reviewed in a previous paper. However, these authors have identified many structural properties of layered and trigonal-prismatic interstitial sites, respectively.…”
Section: Layered Transition-metal Oxidessupporting
confidence: 63%
“…8,13,22,23 Fe 4+ in this compound was observed by Yue et al, 18 and other work also showed oxidation of Fe 3+ to Fe 4+ below 4 V. 6,8,13 We found the latter in Figure S1. Thus, the reversible and irreversible plateaus at 2.8 and Figure 3c may originate from the O3-P3 transition and Fe 4+ migration, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…The XAS result suggests that Ti likely remains inert while other transition metals can be redox-active upon cycling. 18 we obtain improved capacity at this rate, which may result from different electrode preparation methods and/or electrolytes used. An average decay rate of the discharge capacity plotted in Figure 3b is 0.55% per cycle.…”
mentioning
confidence: 92%
“…[214] The transition metal ratio control strategy was applied to the P2-Na 2/3 Mn 1/3 Fe 1/3 Co 1/3 O 2 cathode, for which stable cyclic behavior was obtained by limiting the voltage cutoff to 4.1 V versus Na + /Na. [215] In addition, the electrochemical properties of Ni/Co/Fe-based O3-NaNi 1/3 Co 1/3 Fe 1/3 O 2 [216] and O3-Na(NiCoFeTi) 1/4 O 2 [217] were also explored as cathode materials for SIBs.…”
Section: Wwwadvenergymatdementioning
confidence: 99%